A supportive and inclusive education that prepares: a deeper look at students with learning challenges and the support systems a Catholic, all-male, school provides for teachers to educate those students - MacKenzie, Sean M. (My University, 2025)
There has been a great deal of research conducted examining how academic and social supports in schools, along with individualized accommodations, have helped to aid the education of students with learning challenges. There has also been research done in the response of Catholic schools to the education of students with learning challenges. This study examines the perspectives of teachers, in a private, Catholic, all-male, secondary school, and those teachers’ perceptions of the support they receive from their school when working with these students. It examines teachers’ perceptions about the access to resources, materials, and professional development that support students with learning challenges and how teachers’ differentiated instruction and non-academically related experiences provide academic and social support to all learners. It also specifically looks at how a private, Catholic, all-male, secondary school model impacts the perception of inclusion classrooms. This study concludes that inclusion is essential to Catholic education, and that private, Catholic, all-male, secondary schools have an obligation to have classrooms that include students with learning challenges. It also suggests differentiated instruction is beneficial to students with learning challenges and their educational experiences. Finally, it concludes though there are existing supports, such as educational personnel and teacher preparedness, there needs to be improvement in making these supports more effective and available for the teachers themselves.
Keywords: Learning challenges; Supports; Preparedness; Differentiation; Catholic; All-male